2023
DOI: 10.1109/access.2023.3252566
|View full text |Cite
|
Sign up to set email alerts
|

The Rising Trends of Smart E-Commerce Logistics

Abstract: Smart Logistics (SL) offers a competitive advantage for e-commerce by utilizing Information and Communication Technologies (ICT) such as IoT, AI, Blockchain, Cloud computing, 5G, etc. This technology automates, optimizes, and enables real-time tracking and monitoring of shipments, predicts, and prevents delays, and optimizes delivery routes and schedules. It also provides greater visibility and control, allowing e-commerce businesses to react quickly and efficiently to changes in demand or supply. The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 79 publications
0
10
0
5
Order By: Relevance
“…It is indicated that the choice of a digital platform for e-commerce determines the choice of a logistics activity model. Kalkha et al (2023) also stated that ecommerce requires not only the creation of etrading logistics but also the creation of a network multi-channel system for supporting logistics processes that are simple and reliable to use. Bulakh (2023) stated that the viability of an e-commerce enterprise is primarily determined by the reliability and innovative nature of its cyber security system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is indicated that the choice of a digital platform for e-commerce determines the choice of a logistics activity model. Kalkha et al (2023) also stated that ecommerce requires not only the creation of etrading logistics but also the creation of a network multi-channel system for supporting logistics processes that are simple and reliable to use. Bulakh (2023) stated that the viability of an e-commerce enterprise is primarily determined by the reliability and innovative nature of its cyber security system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect of digitization on trade logistics in e-commerce, highlighting the importance of smart logistics for the sector was examined [10]. In order to evaluate the maturity of research in this field, the researchers looked through 288 publications that were published in the last ten years in the Scopus database.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…The next generation of industrial revolution requires a wide range of developments regarding sensing and perception technologies which would enable intelligent systems for warehousing applications [1]- [3]. These systems should be endowed with high flexibility and versatility to adapt to the rapidly changing market needs.…”
Section: Introductionmentioning
confidence: 99%